IMPLEMENTASI PROGRAM KELUARGA BERENCANA OLEH PERWAKILAN BADAN KEPENDUDUKAN DAN KELUARGA BERENCANA NASIONAL (BKKBN) PROVINSI RIAU TAHUN 2018-2020 - Afriani Maisyarah; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Broadly speaking, Family Planning Population is wrong an effort from the central government through the BKKBN to mobilize people live more prosperous and quality by using the Budget State Income and Expenditures (APBN). Based on Law Number 52 2009 concerning Population Development and Family Development in article 53 paragraphs 1 and 2 says that BKKBN is an institution Non-Ministry Government (LPNK) which is under the President and responsible to the President. For population control the Family Planning Population and Development program Family (KKBPK), which at the end of 2019 BKKBN packed KKBPK became the Family, Population and Family Development Program Berplan which is abbreviated as Proud Kencana. The purpose of this research is to know the Implementation of the Family program Planning by Representatives of the Population and Family Planning Agency National Program (BKKBN) for Riau Province in 2018-2020. In this study the author using a type of descriptive research with a qualitative approach. Location This research was conducted in the city of Pekanbaru and data collection at the Representative Office Provincial National Population and Family Planning Agency (BKKBN) Riau. Data collection techniques carried out are through interviews and documentation. The data analysis technique used is the data analysis model. The results of this study are increasing population growth increasing is a problem that occurs in Riau at this time. In this research using indicators according to Brinkerhoff & Crosby. But there are some variables that do not run optimally such as lack of development constituencies, the lack of accumulation and mobilization of resources and action resulted in many people not knowing the importance of family planning. However BKKBN Representative for Riau Province carried out innovative activities with KIE for the community to participate in the implementation of the program. Like the implementation of the Family Planning program known as Bangga Kencana carried out by the BKKBN Representative for Riau Province controlled population explosion. But the phenomenon is happening now the program is not running well. Another obstacle is the lack of mobile service cars that are carried out and the lack of a team working KB operational. Keywords: Policy, Family Planning Program, Population